Emerging zoonoses and social-economic impact in India - A review - Sherikar, A T; Waskar, V S (The Indian Journal of Animal Sciences, 2005)
Emerging and re-emerging zoonoses are newly recognized diseases or are newly evolved, or have occurred previously but have more recently shown an increase in incidence or expansion into a new geographic, host or vector range. Many new human pathogens that have emerged or reemerged worldwide originated from animals or from products of animal origin. The emergence of zoonotic diseases is associated with a range of underlying causal factors, represents a global threat to human and animal health.They hamper agricultural production, decrease availability of food and create barriers to trade. In India, livestock are important in supporting the livelihoods of poor farmers, consumers, traders and labourers throughout the country. Close association between human population groups and animals, consumption of unpasteurized milk and dairy products, intensification of animal production and increased trade of animals and animal products, the large number of stray dogs, illegal slaughtering and inappropriate waste disposal are some of the principle factors perpetuating infection in humans. Emergence or re-emergence of these diseases requires long-term actions from the veterinary sector to decrease incidence among disease hosts and reduce or interrupt transmission with commitment between the health sector and veterinary sector to implement common control programmes. A close collaboration is needed between animal keepers, farmers, veterinarians and other health professionals, including epidemiologists, occupational health workers, food technologists, specialists in enviromental control and laboratory personnel.